2019
DOI: 10.1021/acs.jmedchem.9b00157
|View full text |Cite
|
Sign up to set email alerts
|

C-6α- vs C-7α-Substituted Steroidal Aromatase Inhibitors: Which Is Better? Synthesis, Biochemical Evaluation, Docking Studies, and Structure–Activity Relationships

Abstract: C-6α and C-7α androstanes were studied to disclose which position among them is more convenient to functionalize to reach superior aromatase inhibition. In the first series, the study of C-6 versus C-7 methyl derivatives led to the very active compound 9 with IC50 of 0.06 μM and K i = 0.025 μM (competitive inhibition). In the second series, the study of C-6 versus C-7 allyl derivatives led to the best aromatase inhibitor 13 of this work with IC50 of 0.055 μM and K i = 0.0225 μM (irreversible inhibition). Beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…Moreover, it was found to have a moderate cytotoxic activity against the breast cancer cell line MCF-7, with an IC 50 value of 14.26 ± 0.40 µM when compared with doxorubicin as a positive control (8.65 ± 0.03 µM). This cytotoxic activity against the mentioned types of estrogen-responsive cancers, cervical cancer and breast cancer [ 41 ] was confirmed by the previously discussed docking study by blocking the aromatase enzyme that synthesizes estrogens.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, it was found to have a moderate cytotoxic activity against the breast cancer cell line MCF-7, with an IC 50 value of 14.26 ± 0.40 µM when compared with doxorubicin as a positive control (8.65 ± 0.03 µM). This cytotoxic activity against the mentioned types of estrogen-responsive cancers, cervical cancer and breast cancer [ 41 ] was confirmed by the previously discussed docking study by blocking the aromatase enzyme that synthesizes estrogens.…”
Section: Resultssupporting
confidence: 69%
“…It can be observed generally through looking at the best score poses that binding of the new ergosterol, thalassosterol ( 1 ), at the active site is similar to that of the endogenous aromatase substrate, exemestane [ 41 ]. The binding interaction shows that the steroidal nucleus, overlapped with the hydrophobic environment of the binding pocket with ring D, is oriented towards the Met 374 residue and the β -face positioned towards the heme moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Allopregnanolone (3α-hydroxy-5α-pregnan-20-one) was prepared from isopregnanolone by a two-step inversion of 3-hydroxy configuration using Mitsunobu reaction via 3α-formate followed by hydrolysis 44 . Androstenediol (androst-5-ene-3β,17β-diol) was prepared by the reduction of dehydroepiandrosterone by sodium borohydride 45 . 5α-Androstenedione (5αandrostane-3,17-dione) was prepared by hydrogenation of dehydroepiandrosterone, followed by oxidation of 3β-hydroxy group 46 .…”
Section: Discussionmentioning
confidence: 99%
“…C6-substituted compounds generally showed a higher HA inhibitory activity with respect to the corresponding C7 derivatives, and docking analysis showed that the substituent in position 6 was able to better fit into the access channel of HA, and thus to better interact with the enzyme, with respect to the same substituent on C7. From this study, Another study evaluating the effect of substitutions in positions 6 and 7 of the steroid core was performed by Roleira et al [57]. Starting from the hit compounds identified in their previous works [58][59][60] (in which a double bond or epoxide functions were inserted in different positions of ring A), new series of compounds were synthesized (Figure 8) carrying methyl, hydroxyl or allyl groups at C6 or C7 positions of the steroid backbone.…”
Section: Potential Fine Tuning Of Ha Enzymatic Activity Through Allosmentioning
confidence: 99%
“…Recently, the mechanism of the antitumor effects of some of the steroidal AIs earlier described by Roleira [57] was evaluated, and the potential involvement of the modulation of steroid receptors, in particular estrogen and androgen receptors (AR), was investigated [69]. For this purpose, cells were treated with the tested compounds plus the SERD fulvestrant or the AR antagonist casodex (CDX), and it was observed that the activity of some compounds (16-19, Figure 12) was reduced in these assay conditions.…”
Section: Multipotent Agents Targeting Both Ha and Ersmentioning
confidence: 99%